TREATMENT OF INGUINAL HERNIA IN A MIXED BREED DOG: A CASE REPORT - I Gede Galyes Pranadinata; I Wayan Wirata; I Gusti Agung Gde Putra Pemayun (Fakultas Kedokteran Hewan Universitas Udayana, 2024)
An inguinal hernia is a protrusion of an organ or part of an organ, fat or tissue through the inguinal ring. This disease is congenital or acquired through trauma. The aim of writing this article is to find out how to diagnose, manage and treat cases of inguinal hernia in dogs. The case animal is a six year old female mixed breed dog, weighing 9.8 kg with complaints of swelling in the abdomen. Radiographic results showed that there was a pocket in the inguinal area containing intestines, so the dog was diagnosed as a case of inguinal hernia with a fausta prognosis. The surgical procedure is carried out by laparotomy by repositioning the contents of the hernia into the abdominal cavity. After surgery, the dog was given the antibiotic cefotaxime and the anti-inflammatory meloxicam intravenously for three days, then continued with the oral antibiotic cefadroxil monohydrate for four days and meloxicam for two days. On the tenth day, the surgical wound has healed, as indicated by the wound being dry, the skin is together, not swollen, and the dog is active. Dogs diagnosed with an inguinal hernia should be treated as soon as possible to prevent the hernia ring from widening and any harmful health effects.